Stenting versus medical treatment in patients with symptomatic vertebral artery stenosis: a randomised open-label phase 2 trial. Issue 6 (June 2015) - Compter, Annette; van der Worp, H Bart; Schonewille, Wouter J; Vos, Jan Albert; Boiten, Jelis; Nederkoorn, Paul J; Uyttenboogaart, Maarten; Lo, Rob T; Algra, Ale; Kappelle, L Jaap; ,
Summary: Background: Patients with a recent vertebrobasilar transient ischaemic attack or ischaemic stroke and vertebral artery stenosis of at least 50% have a high risk of future vertebrobasilar stroke. Stenting of vertebral artery stenosis is promising, but of uncertain benefit. We investigated the safety and feasibility of stenting of symptomatic vertebral artery stenosis of at least 50%, and assessed the rate of vascular events in the vertebrobasilar supply territory to inform the design of a phase 3 trial. Methods: Between Jan 22, 2008, and April 8, 2013, patients with a recent transient ischaemic attack or minor stroke associated with an intracranial or extracranial vertebral artery stenosis of at least 50% were enrolled from seven hospitals in the Netherlands in a phase 2 open-label trial with masked assessment of outcome. Patients were randomly allocated in a 1:1 ratio to stenting plus best medical treatment or best medical treatment alone by the local investigators using a web-based randomisation system. The primary outcome was the composite of vascular death, myocardial infarction, or any stroke within 30 days after the start of treatment. The secondary outcomes were stroke in the supply territory of the symptomatic vertebral artery during follow-up, the composite outcome during follow-up, and the degree of stenosis in the symptomatic vertebral artery at 12 months. The trial is registered, number ISRCTN29597900. Findings: The trial was stopped after inclusion of 115 patients because of new regulatory requirements, including the use of a few prespecified stent types and external monitoring, for which no funding was available. 57 patients were assigned to stenting and 58 to medical treatment alone. Three patients in the stenting group had vascular death, myocardial infarction, or any stroke within 30 days after the start of treatment (5%, 95% CI 0–11) versus one patient in the medical treatment group (2%, 0–5). During a median follow-up of 3 years (IQR 1·3–4·1), seven (12%, 95% CI 6–24) patients in the stenting group and four (7%, 2–17) in the medical treatment group had a stroke in the territory of the symptomatic vertebral artery; 11 (19%) patients in the stenting group and ten (17%) in the medical treatment group had vascular death, myocardial infarction, or any stroke. The small size of the vertebral artery and stent artifacts did not allow exact grading of restenosis on CT angiography. During the complete period of follow-up, there were 60 serious adverse events (eight strokes) in the stenting group and 56 (seven strokes) in the medical treatment alone group. Interpretation: Stenting of symptomatic vertebral artery stenosis is associated with a major periprocedural vascular complication in about one in 20 patients. In the population we studied, the risk of recurrent vertebrobasilar stroke under best medical treatment alone was low, questioning the need for and feasibility of a phase 3 trial. Funding: Dutch Heart Foundation.